Analysis of pantaprazole na monohydrate and sesquihydrate by powder x-ray diffraction (PXRD) - Mahajan, Devidas T.; Mohmad, Noor; Raut, D. M.; Gajbhiye, Jayant M. (Journal of Medicinal Chemistry and Drug Discovery, 2015)
Pantaprazole Na monohydrate and sesquihydrate were characterized by PXRD.significant difference in the diffraction patterns of Pantaprazole Na hydrates. The sesquihydrate contains all the diffraction peaks of monohydrate in addition to peaks.